Kearifan Lokal Masyarakat Suku Bugis di Daerah Karangantu Provinsi Banten - Armida Armida; Dwinarti Marbun; Ervina Rahayu; Muhammad Yusuf Ammar; Najwa Bening Putri; Nayla Anwar Putri; Stevana Ruthia Simbolon; Tuki Pranata (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research examines the local wisdom of the Bugis tribal community in Karangantu, Banten Province, focusing on four main aspects: monetary panai, mapasili traditions, mattampung, and traditional houses. The research method used is qualitative and based on observations and in-depth interviews with local community members. Research findings show that panai money functions as a symbol of the husband's respect and responsibility towards the married woman, as well as a reflection of the family's social status. The mapasili tradition, performed three days after death, aims to purify the house and clothes of the deceased as a sign of respect towards the ancestors. In addition, the mattampung tradition reflects strong social and cultural values within the community, while the traditional Bugis house in Karangantu is also a symbol of cultural identity that needs to be preserved. This research shows that despite the influence of modernization, the Bugis people still maintain these traditions as an integral part of their identity that must be preserved for future generations. These findings shed light on how local wisdom can adapt and survive in changing times.